Exploring public sentiments towards courier services in Malaysia through Twitter: a sentiment analysis approach - Mohamed Imran Mohamed Ariff; Rasyidin Muhammad Zaharin Raja Salim; Azilawati Azizan; Samsiah Ahmad; Noreen Izza Arshad; Mohammad Nasir Abdullah (Institute of Advanced Engineering and Science, 2024)
This study delves into the sentiment analysis of courier services in Malaysia through the lens of tweets. With the escalating reliance on courier services for daily parcel deliveries, understanding public sentiment becomes imperative. Through a systematic methodology encompassing data gathering, preparation, alteration, analysis, modeling, and deployment, this study aims to furnish valuable insights and recommendations. A dynamic graphical representation of sentiment scores is presented for intuitive interpretation and informed decision-making. The study's significance lies in empowering Malaysians to make judicious choices regarding courier services, thereby fostering transparency in the industry. The study proposes several avenues for future enhancements, including the integration of autocorrect features, diversifying data sources and languages, incorporating deep learning techniques, and developing a user-friendly interface for enhanced visualization. This study serves as a guiding resource, illuminating sentiments surrounding courier services in Malaysia and paving the way for future advancements in sentiment analysis within this domain.